Revitalizing Arts Education Through Community-Wide Coordination - Bodilly, Susan J. (RAND Corporation, 2008)
Initiatives to coordinate schools, cultural institutions, community-based organizations, foundations, and/or government agencies to promote access to arts education in and outside of schools have recently developed. This study looks at the collaboration efforts of six urban communities: how they started and evolved, the kinds of organizations involved, conditions that helped and that hindered coordination, and strategies used.